GRECO-ROMAN FRAMEWORKS USED IN THE HANDWRITTEN AND PRINTED TRADITIONS BETWEEN THE 16TH AND 19TH CENTURIES IN BRAZIL - Moraes, Carlos Eduardo Mendes de [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
During the 16th, 17th and 18th centuries, the practice of imitation/emulation/reference in relation to the classic authors from Greco-Roman Antiquity prevailed as a rule in literate and scientific writing in Portugal and in its provinces. This practice worked as the official written communication among those locations, and its configuration was based on ancient rhetoric and poetry, exploring from them mainly the ornament, comparison, argument of authority, besides of several other possibilities. This practice is recorded both in the printed tradition and in the manuscript tradition of formal Portuguese writing, and, especially, in writings with literary intention. It can be evidenced not just by the profusion of references, imitations, quotations and reconstructions of episodes and characters, but also by the quotations or comparisons between ancient literature and people from the court or patrons-which were referred in paratexts traditionally produced by writers, editors, evaluated by censors, and recognized by readers in requests, deferences, dedications and warnings during submissions of these writing pieces to censorship institutions.
Keywords: Brazilian Literature; Classical Studies; Manuscripts; Portuguese Literature; Printed Tradition; Source